2006
DOI: 10.1080/01443610600720287
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled study of non-closure of peritoneum at caesarean section in a Nigerian population

Abstract: A prospective randomised study of 54 patients undergoing caesarean section was carried out to determine if non-closure of peritoneum at lower segment caesarean section has advantages over suture peritonisation with regard to postoperative morbidity. A total of 27 women were randomised to closure and 27 to non-closure of peritoneum. Management decisions were made without reference to treatment groups. Statistical analysis compared the outcome between the two groups. The results revealed that anaesthesia and ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…Surgical peritoneal closure resulted in more advanced adhesion formation. The practice of peritoneum nonclosure should be observed at cesarean delivery [34].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical peritoneal closure resulted in more advanced adhesion formation. The practice of peritoneum nonclosure should be observed at cesarean delivery [34].…”
Section: Discussionmentioning
confidence: 99%
“…Three trials involving 889 women showed no reduction in postoperative fever (average RR 0.60, 95% CI 0.29 to 1.27; Heterogeneity: Tau² = 0.28; Chi² = 6.26, df = 2; P = 0.04); I² = 68%), Analysis 2.3 , and two showed a reduction in wound infection (RR 0.36, 95% CI 0.14 to 0.89), Analysis 2.2 . There was no difference in the one trial (Weerawetwat 2004 ), that assessed for endometritis, (RR 3.00, 95% CI 0.12 to 72.91), Analysis 2.4 .…”
Section: Methodsmentioning
confidence: 99%
“…In two trials involving 157 women, adhesions formation was increased in the visceral peritoneal non-closure group (Malvasi 2009 ; Weerawetwat 2004 ) (RR 2.49 and 95% CI 1.49 to 4.16), Analysis 2.1 . This effect was seen only in one of the trials (Malvasi 2009 ), which was at high risk of bias.…”
Section: Methodsmentioning
confidence: 99%
“…Otros estudios no encontraron diferencias en el número de dosis de analgesia parenteral, pero si encontraron una menor cantidad de necesidad de analgesia de rescate en el grupo que no se realizó el cierre y disminución significativa en la necesidad de analgesia con opiáceos 16,22 . Malomo et al 23 reportaron menor uso de analgesia narcótica en las pacientes en las cuales no se realizaba la peritonización. Una investigación previa no encontró diferencias entre los grupos con respecto al dolor postoperatorio, pero la movilización e ingesta oral fueron significativamente más temprana en el grupo sin cierre peritoneal 24 .…”
Section: Discussionunclassified
“…Varios estudios no han demostrado diferencias en la frecuencia de fiebre post-operatoria, endometritis o infección de la herida quirúrgica 15,16,20 . Contrario a lo previamente expuesto, otras dos investigaciones encontraron disminución significativa en la frecuencia de morbilidad febril en las pacientes que no se realizó la peritonización, sin diferencias en la incidencia de endometritis o infección del tracto urinario 23,26 . El meta-analisis previamente citado, demostró que la morbilidad febril, endometritis e infección de la herida fue menor en el grupo en el que no se realizó el cierre, aunque esta diferencia no fue significativa 1 .…”
Section: Discussionunclassified